The Dalton quantum chemistry program system. (23rd September 2013) - Aidas, Kestutis; Angeli, Celestino; Bak, Keld L.; Bakken, Vebjørn; Bast, Radovan; Boman, Linus; Christiansen, Ove; Cimiraglia, Renzo; Coriani, Sonia; Dahle, Pål; Dalskov, Erik K.; Ekström, Ulf; et al.
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>